2017
DOI: 10.2967/jnumed.117.193888
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Uptake of 64Cu-DOTA-Trastuzumab in Patients with Metastatic Breast Cancer

Abstract: The goal of this study was to characterize the relationship between tumor uptake of Cu-DOTA-trastuzumab as measured by PET/CT and standard, immunohistochemistry (IHC)-based, histopathologic classification of human epidermal growth factor receptor 2 (HER2) status in women with metastatic breast cancer (MBC). Women with biopsy-confirmed MBC and not given trastuzumab for 2 mo or more underwent complete staging, includingF-FDG PET/CT. Patients were classified as HER2-positive (HER2+) or -negative (HER2-) based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 15 publications
2
62
0
Order By: Relevance
“…For this reason, it is important to evaluate HER2 expression before HER2-targeted therapy in order to enhance the treatment e cacy of the patients. 64 Cu-DOTA-Trastuzumab PET, one of the methods for evaluating HER2 expression in a non-invasive method, was reported as a feasible modality with clinical trials [5,6,13,14]. Compared to other PET agents, such as 89 Zr and 124 I, which have been used for evaluating HER2 expression, 64 Cu has the bene t of reducing radiation exposure with a relatively short half-life [2], and also has the advantage of being able to perform PET/CT in an outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, it is important to evaluate HER2 expression before HER2-targeted therapy in order to enhance the treatment e cacy of the patients. 64 Cu-DOTA-Trastuzumab PET, one of the methods for evaluating HER2 expression in a non-invasive method, was reported as a feasible modality with clinical trials [5,6,13,14]. Compared to other PET agents, such as 89 Zr and 124 I, which have been used for evaluating HER2 expression, 64 Cu has the bene t of reducing radiation exposure with a relatively short half-life [2], and also has the advantage of being able to perform PET/CT in an outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…The trials were able to demonstrate that they can quantify HER2 expression of lesions in patients with HER2 expressing tumors [9,11,12]. In addition, the use of HER2 targeted PET imaging using 64 Cu-tetra-azacyclododecanetetra-acetic acid (DOTA)-Trastuzumab has been attempted [5,6,11,13,14]. Clinical trials using this agent in the United States and Japan showed effective identi cation of HER2 expression in breast cancer patients [5,6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials worldwide have reported the efficacy of using 64 Cu-DOTA-trastuzumab to measure expression of the human epidermal growth factor 2 (HER2/neu) in breast cancer patients. [32][33][34] In addition, 64 Cu-labeled cetuximab for imaging epidermal growth factor receptor has been studied extensive in preclinical work with experiments comparing the performance of different chelates including DOTA, 35,36 CB-TE1A1P, and CB-TE1K1P in combination with either tradition amide bond coupling or "copper-free click" methods for rapid bioconjugation. 37 As efforts gather pace to improve access to 67 Cu, 18 identification of new chelates, linkers, and radiolabeling methods to produce 64/67 Cu-mAbs is essential.…”
Section: Copper Radiolabeled Antibodiesmentioning
confidence: 99%
“…That said, this has not stopped several laboratories from bringing 64 Cu-labeled immunoPET agents into the clinic. [99][100][101] The in vivo metabolism of both 64 Cu-and 67 Culabeled antibodies has been studied in several preclinical mouse models. [102][103][104] Yet regardless of the antibody or tumor model, the catabolism of the antibody in the tumor was found to be fast and led to the formation of a final product consisting of the radiocopper-chelator complex attached to a short protein trapped within the lysosome.…”
Section: The Isotopes Of Coppermentioning
confidence: 99%